Solid-state thermal and spectroscopic studies of the anti-inflammatory drug sulindac using UV-Vis, MIR, NIR, DSC, simultaneous TG-DSC, and the coupled techniques TG-EGA-MIR and DSC-optical microscopy - Guerra, Renan B. [UNESP]; Gálico, Diogo A. [UNESP]; Holanda, Bruno B. C. [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2016)
Simultaneous thermogravimetry-differential scanning calorimetry (TG-DSC), differential scanning calorimetry-optical microscopy (DSC-optical microscopy), online coupled thermogravimetry-infrared spectroscopy evolved gas analyses (TG-EGA-MIR), and spectroscopic techniques were used to study the non-steroidal anti-inflammatory drug sulindac in polymorphic form II. The TG-DSC curves, which were performed with the aid of DSC-optical microscopy, provided information concerning the thermal stability and decomposition profiles of the compound. From the TG-EGA-MIR coupled technique, it was possible to identify formaldehyde as a volatile compound that was released during thermal decomposition. A complete spectroscopic characterization in the ultraviolet, visible, near- and middle-infrared regions was performed in order to understand the spectroscopic properties of sulindac form II.
Keywords: Coupled TG-EGA-MIR; DSC-optical microscopy; Spectroscopic studies; Sulindac; Thermal behavior